The Principal’s Leadership in Improving Teachers’ Performance at MTs Al- Azhar Teluk Sentosa - Hirwansyah, Hirwansyah; Rifai, Muhammad; Fatkhurrohman, Fatkhurrohman (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines the effectiveness of madrasah principal leadership in improving teacher performance at MTs Al-Azhar Teluk Sentosa, addressing issues of teacher absenteeism, mismatched subject assignments, and suboptimal teaching quality. Using a qualitative descriptive approach, data were collected through observation, interviews (with 1 principal, 3 vice principals, and 3 teachers), and documentation at Jl. Besar Ajamu, Teluk Sentosa Village. Findings reveal that democratic leadership fostering collegial relationships significantly enhances teacher performance. While persistent challenges remain (including tardiness and qualification mismatches), regular training and supervision by the principal have effectively mitigated these issues. The study uniquely demonstrates how democratic leadership in rural Indonesian madrasahs creates familial work environments that improve performance despite resource constraints. Results suggest that school leaders should: (1) adopt participatory decision-making, (2) implement ongoing teacher mentoring programs, and (3) maintain consistent supervision to address performance gaps. This research provides a model for balancing authoritative guidance with collaborative leadership in Islamic educational institutions, offering actionable strategies for under-resourced settings.